Dose-response of intermittent theta burst stimulation of the prefrontal cortex: A TMS-EEG study. (April 2022) - Desforges, Manon; Hadas, Itay; Mihov, Brian; Morin, Yan; Rochette Braün, Mathilde; Lioumis, Pantelis; Zomorrodi, Reza; Théoret, Hugo; Lepage, Martin; Daskalakis, Zafiris J.; Tremblay, Sara
Highlights: The effects of 600, 1200 and 1800 pulses of intermittent theta burst stimulation were compared in healthy volunteers. None of the three doses was superior in modulating prefrontal evoked activity and oscillatory activity. iTBS may act on dorsolateral prefrontal cortex activity via the modulation of excitation/inhibition balance. Abstract: Objective: Using concurrent transcranial magnetic stimulation (TMS) and electroencephalography (TMS-EEG), this study aims to compare the effect of three intermittent theta-burst stimulation (iTBS) doses on cortical activity in the left dorsolateral prefrontal (DLPFC) cortex. Methods: Fourteen neurotypical participants took part in the following three experimental conditions: 600, 1200 and 1800 pulses. TMS-EEG recordings were conducted on the left DLPFC pre/post iTBS, including single-pulse TMS and short- and long-interval intracortical inhibition (SICI, LICI). TMS-evoked potentials (TEP) and event-related spectral perturbation (ERSP) were quantified. Linear mixed models were used to assess the effect of iTBS on brain activity. Results: The effects of iTBS on DLPFC activity did not significantly differ between the three doses. Specifically, regardless of dose, iTBS modulated the amplitude of most TEP components (P30, N45, P60, P200), reduced SICI and LICI ratios of P30 and P200, and decreased ERSP power of theta oscillations. Conclusions: In neurotypical individuals, doubling or tripling the number of iTBS pulses does not result in stronger potentiation of prefrontal activity. However, all iTBS conditions induced significant modulations of DLPFC activity. Significance: Replicating the study in clinical populations could help define optimal parameters for clinical applications.